Aplikasi Teori Batas Terhadap Poligami (Studi Hermeneutika Muhammad Syahrur) - Jendri Jendri (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2020)
This article seeks to provide an interpretation of the polygamy verse contained in the Qur’an Surah An-Nisa: 3 with Muhammad Syharur’s hermeneutic approach or Limit Theory. Polygamy discourse is an interesting issue since then until now. The polygamy verse became an interesting topic so that gave birth to various interpretations on it from classical interpretations, feminism to contextual interpretations. This article shows that based on the practice of polygamy according to Syahrur can be done with the provisions of two restrictions, namely quantitative and qualitative boundaries. Both of these limits must be applied simultaneously. The general understanding of polygamy in terms of quantitative restrictions is that a person marries at least one woman without the requirement of a widow or a virgin, and the maximum limit is four women. The understanding of polygamy in the theory of boundaries in terms of qualitative and quantitative boundaries is that a person marries a woman as a minimum limit with no requirement whether a widow or a virgin. Marrying two or three women is included in the area of ijtihad on the condition that they must have orphans. but the maximum limit is four women with the condition of widows who have orphans.